The Development of the Principle of Non-Intervention in International Jurisprudence: A Critical Analysis of its Normative Scope and Judicial Interpretation - Budzianowska, Dobrosława (Polish Review of International and European Law, 2025)
This article offers a critical analysis of the principle of non-intervention in international jurisprudence, situating it as a functional corollary of state sovereignty and examining how coercion operates as the legal threshold that transforms influence into unlawful interference. Focusing on the jurisprudence of the International Court of Justice (ICJ) and other judicial bodies, the article traces how the legal contours of non-intervention have been developed, interpreted, and, at times, left unresolved. Although widely recognised in both treaty and customary law, the principle’s judicial articulation remains uneven, particularly in relation to the definition of coercion, the attribution of indirect conduct, and the treatment of emerging forms of interference. Using a doctrinal and historical-legal method, the article analyses key decisions including Corfu Channel, Nicaragua, and Armed Activities, alongisde relevant regional jurisprudence. The article concludes that addressing the principle’s normative fragility requires a more coherent legal framework, one that integrates judicial interpretation, doctrinal clarification, and institutional engagement. Ensuring the relevance of the principle of non-intervention requires that it be capable of addressing the complex forms of pressure and influence that shape contemporary international relations.